INDONESIAN GOVERNMENT POLICY AND SMEs BUSINESS STRATEGY DURING THE COVID-19 PANDEMIC - Ratnaningsih Hidayati; Nadya Megawati Rachman (Niagawan, 2021)
Economic disruption by The COVID-19 pandemic has hit Indonesian economic heavily. The purpose of this study is to provide an overview of government policies and business strategies in Indonesia amid the COVID-19 pandemic. This study employed a qualitative approach with data sources of literature reviews. The results of the study indicate that the Indonesian Government has responded to the pandemic by issuing some policies regarding SMEs.  There are several policies issued regarding the Micro and SMEs business. The policy is breakdown into five schemes namely (1) Social support; (2) SMES tax incentives; (3) Credit restructuring and relaxation (4) Working capital support stimulus; and (5) Collaboration with State-owned enterprise as the  off-taker for SMES products. On the other hand, there are some SMES business strategies in adjusting amidst the Covid-19 pandemic in Indonesia. Those strategies are (1) Products innovation; (2) Customer and stakeholder relationship management;(3) Digital marketing and distribution; and (4) Strategic Agility.